2004
DOI: 10.2527/2004.82113254x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative environments decrease tenderization of beef steaks through inactivation of μ-calpain1

Abstract: This study was designed to test the hypothesis that oxidative conditions in postmortem (PM) tissue decrease calpain activity and proteolysis, subsequently minimizing the extent of tenderization. To achieve different levels of oxidation, the diets of beef cattle were supplemented with vitamin E for the last 126 d on feed, and beef steaks were irradiated early PM. Ten steers were fed a finishing diet with the inclusion of vitamin E at 1,000 IU per steer daily (VITE). Another 10 beef steers were fed the same fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(137 citation statements)
references
References 32 publications
5
123
0
9
Order By: Relevance
“…5). The presence of intact titin in aged samples is a novel result because titin is typically degraded earlier postmortem by calpain-1 (Huff- Lonergan et al, 1995;Taylor et al, 1995;Melody et al, 2004;Rowe et al, 2004b). The rate of titin degradation is known to be slower in beef that exhibits high-shear-force values regardless of animal age or gender (Huff-Lonergan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The presence of intact titin in aged samples is a novel result because titin is typically degraded earlier postmortem by calpain-1 (Huff- Lonergan et al, 1995;Taylor et al, 1995;Melody et al, 2004;Rowe et al, 2004b). The rate of titin degradation is known to be slower in beef that exhibits high-shear-force values regardless of animal age or gender (Huff-Lonergan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of desmin changes the secondary structure of desmin, which increases susceptibility to proteolysis by caspases (Chen et al, 2014). Oxidation is also known to decrease the activity of calpain-1, ultimately reducing desmin degradation by calpain-1 (Rowe et al, 2004b;Carlin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that a postmortem oxidative environment interferes with proteolysis thus hindering the tenderization process (Guttmann and Johnson, 1998;Lametsch et al, 2008;Rowe et al, 2004). Pogge et al (2014b) recently reported feedlot diets containing 0.55% S (40% dried DGS diets, with sodium sulfate providing additional S) negatively altered the autolysis of the muscle protease µ-calpain, reflected by a greater percentage of the 80-kDa subunit (+9.4%) and a lesser quantity of the 76-kDa subunit (-10.5%) when compared to steers consuming diets containing 0.22% or 0.34% S. These data indicate that less autolysis was occurring in the high S diet, which in turn may explain the observed tendency for a lesser extent of troponin T degradation within the high S treatment.…”
Section: Effects On Carcass and Meat Characteristicsmentioning
confidence: 99%
“…This means that the metabolic stress created by food restriction followed by refeeding was not sufficient to modify the oxidation level of proteins in animals at slaughter. Consequently, in our study, an alteration of protein oxidation during the compensatory growth process in vivo cannot be responsible for an altered protease activity during meat aging in animals undergoing compensatory growth (Maltin et al, 2003;Rowe et al, 2004a and2004b). However, proteins (and hence the proteases) still undergo oxidation during maturation, its intensity being highly dependent on the antioxidants present in the muscles and meat (Martinaud et al, 1997;Mercier et al, 1998;Rowe et al, 2004a).…”
Section: Resultsmentioning
confidence: 67%
“…Increased proteases oxidation reduces the functional properties of these proteases and decreases their efficiency in the meat protein maturation process (Rowe et al, 2004a and2004b). Consequently, it can be hypothesized that some in vivo oxidation processes in the muscles may have an impact on the enzymes activities and protein structure both in vivo and post mortem (Stadtman and Levine, 2000).…”
Section: Introductionmentioning
confidence: 99%